Technology Value Cocreation in Healthcare Service: A Literature Review 2020-2025 - Siti Khoirun Nisa; Utomo, Destiawan Eko; Sarfilianty Anggiani (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This literature review examines five years of research (2020–2025) on technology value co-creation in healthcare services, addressing a notable gap in comprehensive syntheses of this evolving domain. Driven by the increasing prominence of digital health technologies, this study systematically analyzes 24 peer-reviewed articles from Emerald and ScienceDirect, categorizing them into five key themes: digital health technologies and mhealth platforms, patient and consumer engagement, organizational and ecosystem-level value co-creation, value co-creation frameworks and conceptual developments, and measurement and evaluation models. Findings reveal that while technology significantly empowers stakeholders and facilitates co-creation, there remains a limited understanding of multi-actor involvement, the active patient role, and the configurational impact of value drivers. The review highlights the inherently socio-technical nature of healthcare value co-creation, emphasizing the need for integrated approaches that consider human-AI entanglement, diverse engagement styles, and adaptive organizational practices. This synthesis contributes to both theory and practice by mapping current trends, identifying critical research gaps, and suggesting future avenues for fostering patient-centered, technology-enabled healthcare solutions.